2016
DOI: 10.4103/1817-1745.181261
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal cranial sonography: A concise review for clinicians

Abstract: Cranial sonography continues to hold an important place in neonatal care. Attributes favorable to sonography that make it almost indispensable for routine care of the newborn includes easy access, low cost, portability, lack of ionizing radiations and exemption from sedation or anaesthesia. Cranial sonography has highest impact in neonates suspected to have meningitis and its complications; perinatal ischemia particularly periventricular leukomalacia (PVL); hydrocephalus resulting from multitude of causes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Patient age and the subtlety of anticipated findings determine the best imaging sequences for reducing patient motion during an MRI exam while simultaneously minimizing the use of anesthesia and sedation. Limited fast MRI with single shot-fast spin echo or half-Fourier acquisition single-shot turbo spin-echo (SSFSE or HASTE; Table 1) is often adequate to evaluate ventricular size in children with known hydrocephalus [6], although ultrasound can be used for the first several months [7]. When evaluating for readily apparent abnormalities such as a large infarct or hemorrhage, sequences that correct for motion but offer relatively low spatial resolution can be used.…”
Section: Preventing Motion Degradationmentioning
confidence: 99%
“…Patient age and the subtlety of anticipated findings determine the best imaging sequences for reducing patient motion during an MRI exam while simultaneously minimizing the use of anesthesia and sedation. Limited fast MRI with single shot-fast spin echo or half-Fourier acquisition single-shot turbo spin-echo (SSFSE or HASTE; Table 1) is often adequate to evaluate ventricular size in children with known hydrocephalus [6], although ultrasound can be used for the first several months [7]. When evaluating for readily apparent abnormalities such as a large infarct or hemorrhage, sequences that correct for motion but offer relatively low spatial resolution can be used.…”
Section: Preventing Motion Degradationmentioning
confidence: 99%
“…Ultrasound examination of the head is used by pediatric neurosurgeons and pediatricians to perform intracranial assessment. 1517 In these examinations, echocardiographic probes are used to inspect the anterior fontanel, which is widely patent. In 1998, Soboleski et al 18 examined excised synostosed suture specimens by high-resolution sonography and reported that the high-resolution sonographic images provided easy means to assess sutural width.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral white matter injury after preterm birth is associated with long-term, adverse neurodevelopmental outcomes ( Hintz et al, 2015 , Allen, 2008 , Aylward, 2005 ). In the past, many children born preterm (PT) had cystic lesions visualized readily on cranial ultrasound and clinical MRI scans ( Gupta et al, 2016 , Inder et al, 1999a ). Advances in neonatal medicine have reduced the rates of cystic injuries, ( Gano et al, 2015 ) but have not eliminated noncystic white matter injury and subsequent white matter dysmaturity ( Volpe, 2009 , Back et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%